Rapid Progression of Extensive Arachnoid Adhesion Longer Than Twelve Segments and Cysts Formation after Posterior Lumbar Interbody Fusion: Case Report - Xumin, Hu; Thapa, Ashish J; Meiguang, Zheng; Huiyong, Shen (Nepal Journal of Neuroscience, 2016)
Arachnoid cysts and intradural adhesion are uncommon in postoperative complication rather than congenital condition. The adhesion and cysts are usually around surgical site but some extend to a distant place. The authors report a case of formation of arachnoid cysts and adhesion far away from original surgical site with signifi cant clinical manifestations after posterior lumbar interbody fusion (PLIF). A 55-year-old woman accepted PLIF and got a good recovery but her dura mater was torn and sutured during procedure. Six months after her 1st surgery, she felt rapid progressing numbness from foot to belly and weakness of both lower limbs. On Examination bilateral deep tendon refl exes were hyperactive. Magnetic resonance imaging (MRI) showed intradural adhesion formed from T4 to sacral canal. Cerebrospinal fluid terminated at T4 level and there exactly the arachnoid cyst was formed. The long intradural adhesion and distant cyst formation made this case unique and the cause of neurological manifestations. Then the patient underwent intradural exploratory surgery and cyst-abdominal shunting. The cyst was actually found to be the terminal part of remaining subarachnoid space. Patient’s numbness stopped advancing upward and the strength of both lower limbs gradually improved after surgery. Therefore, arachnoid cyst and adhesion might appear at any place after spine surgery with dural rupture. Exploratory surgery and timely decompression can effectively slow down the progression of disease. Spinal meningeal cysts are rare and have been described as “arachnoid cysts,” “pouches”, or “diverticula”.7 Most spinal intradural arachnoid cysts are thought to be congenital but still some acquired arachnoid cysts were reported as to be the results of trauma, hemorrhage or infection.8 Even fewer were caused by intradural infl ammation after invasive diagnostic test and treatment. Nepal Journal of Neuroscience. Vol. 13, No. 2, 2016, Page: 94-98